ANALYSIS OF MICRO, SMALL AND MEDIUM ENTERPRISES (MSMES) MARKETING STRATEGIES IN ERA 4.0 - Kadar Nurjaman (Globalwriting Academica Consulting & Publishing, 2019)
Technological developments make various business sectors need to develop so as not to be left behind by other businesses. One business sector must follow technological developments in Indonesia’s micro, small and medium enterprises (MSMEs). This research then aims to see how MSMEs implement marketing strategies by utilizing technology in the digital era 4.0. This research will be carried out using a qualitative approach and data from various research results and previous studies that are still relevant to this research. The results of this study found that MSMEs in Indonesia still have a low contribution compared to the contribution of MSMEs in other countries. This low contribution is caused by the lack of utilization of existing resources by MSME actors in Indonesia, such as using social media to market their products. It is hoped that with the emergence of the digital 4.0 era, MSMEs in Indonesia can use technology well and maximally so that, in the end, MSMEs can develop and make a considerable contribution to the Indonesian state.